Convergence and decay rate to equilibrium of bounded solutions of quasilinear parabolic equations - Chill, Ralph; Fiorenza, Alberto (Journal of Differential Equations, 2006)
We study the convergence and decay rate to equilibrium of bounded solutions of the quasilinear parabolic equation u t − div a ( x , ∇ u ) + f ( x , u ) = 0 on a bounded domain, subject to Dirichlet boundary and to initial conditions. The data are supposed to satisfy suitable regularity and growth conditions. Our approach to the convergence result and decay estimate is based on the Łojasiewicz–Simon gradient inequality which in the case of the semilinear heat equation is known to give optimal decay estimates. The abstract results and their applications are discussed also in the framework of Orlicz–Sobolev spaces.